Harry Potter And The Philosopher's Stone - J.K. Rowling
Harry Potter thinks he is an ordinary boy - until he is rescued by an owl, taken to Hogwarts School of Witchcraft and Wizardry, learns to play Quidditch and does battle in a deadly duel.